A new species of planthopper in the genus Cobacella (Hemiptera: Auchenorrhyncha: Derbidae) from oil palm (Elaeis guineensis) in Costa Rica - Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Helmic, Ericka E.; Bartlett, Charles R.; Bahder, Brian W. (Zootaxa, 2023)
Recent survey work in Costa Rica has revealed a high diversity of planthoppers in the family Derbidae on palms (Arecaceae). During an expedition to Costa Rica in 2021, specimens were collected from African oil palm (Elaeis guineensis) along the pacific coast and determined to represent a new species of derbid in the genus Cobacella. Herein, the novel taxon, Cobacella palmensis sp. n., is described and compared with the two other species in the genus. Supplemental molecular data for the cytochrome c oxidase subunit I (COI) barcoding region, 18S rRNA gene and D9-D10 expansion region of the 28S rRNA gene are provided to test the placement of the novel taxon relative to available otiocerine planthoppers. We also present a preliminary key to the species of Cobacella and review all available specimen records of the genus.